Development of a novel resection and cutting guide for mandibular reconstruction using free fibula flap. Issue 11 (November 2018) - Weitz, Jochen; Wolff, Klaus-Dietrich; Kesting, Marco Rainer; Nobis, Christopher-Philipp
Abstract: Introduction: The authors developed a semi-standardised resection and cutting guide for mandibular reconstruction with free fibula flap based on data of mandible sizes and angles. Methods: After analyzing the angles and lengths of mandibular angles and segments on computer tomography, a partly-adjustable resection guide for the mandible and cutting guide for the fibula were designed. Results: After testing and optimizing the guides on plastic models and cadavers, the guides were successfully used for mandible resection and reconstruction with free fibula flap in 8 patients with segmental mandibulectomy. Application of the cutting and resection guides and functional results like occlusion and aesthetic appearence were satisfactory in all cases. Conclusions: The developed semi-standardised device is a helpful instrument for facilitating reconstruction of segmental mandibular defects with free fibula flaps. No extensive preoperative preparation and 3D printing is necessary which can avoid additional costs for virtual planning. Especially for lower budget health systems this can be an alternative to virtual planning.